Dyslexia in the Music Classroom: A Review of Literature. (October 2019) - Reifinger, James L.
Developmental dyslexia, or specific reading disorder, is a reading impairment characterized by persistent difficulty in word recognition, decoding, and spelling skills in children despite having average or above academic performance in other areas. To increase an understanding of the nature of dyslexia and its relationship to music, this article first discusses the process of typical reading development and how researchers believe this process is impaired for individuals with dyslexia. Dyslexia identification and interventions are then explained. Next, research that shows how music skills may differ for students with dyslexia is presented. Experimental studies have shown that music training has been an effective way to improve reading skills in children with dyslexia. To understand why music training might improve reading ability, the precise auditory timing hypothesis proposed by Tierney and Kraus is discussed, along with implications for music education.